Next‐generation sequencing‐based detection of circulating tumour DNA After allogeneic stem cell transplantation for lymphoma. (6th October 2016) - Herrera, Alex F.; Kim, Haesook T.; Kong, Katherine A.; Faham, Malek; Sun, Heather; Sohani, Aliyah R.; Alyea, Edwin P.; Carlton, Victoria E.; Chen, Yi‐Bin; Cutler, Corey S.; Ho, Vincent T.; Koreth, John; et al.
Summary: Next‐generation sequencing (NGS)‐based circulating tumour DNA (ctDNA) detection is a promising monitoring tool for lymphoid malignancies. We evaluated whether the presence of ctDNA was associated with outcome after allogeneic haematopoietic stem cell transplantation (HSCT) in lymphoma patients. We studied 88 patients drawn from a phase 3 clinical trial of reduced‐intensity conditioning HSCT in lymphoma. Conventional restaging and collection of peripheral blood samples occurred at pre‐specified time points before and after HSCT and were assayed for ctDNA by sequencing of the immunoglobulin or T‐cell receptor genes. Tumour clonotypes were identified in 87% of patients with adequate tumour samples. Sixteen of 19 (84%) patients with disease progression after HSCT had detectable ctDNA prior to progression at a median of 3·7 months prior to relapse/progression. Patients with detectable ctDNA 3 months after HSCT had inferior progression‐free survival (PFS) (2‐year PFS 58% vs. 84% in ctDNA‐negative patients, P = 0·033). In multivariate models, detectable ctDNA was associated with increased risk of progression/death (Hazard ratio 3·9, P = 0·003) and increased risk of relapse/progression (Hazard ratio 10·8, P = 0·0006). Detectable ctDNA is associated with an increased risk of relapse/progression, but further validation studies are necessary to confirm these findings and determine the clinical utility of NGS‐based minimal residual disease monitoring in lymphoma patients after HSCT.